字典翻译 问答 小学 数学 【设f(x)=x^2-∫(下0,上a)f(x)dx,且a是不等于-1的常数,证明:∫(下0,上a)f(x)dx=a^3/(3a+3)】
问题标题:
【设f(x)=x^2-∫(下0,上a)f(x)dx,且a是不等于-1的常数,证明:∫(下0,上a)f(x)dx=a^3/(3a+3)】
问题描述:

设f(x)=x^2-∫(下0,上a)f(x)dx,且a是不等于-1的常数,证明:∫(下0,上a)f(x)dx=a^3/(3a+3)

董丽回答:
  证:   记∫(0,a)f(x)dx=k(常数)   则f(x)=x^2-∫(0,a)f(x)dx可化为   f(x)=x^2-k   两边在[0,a]上积分有   ∫(0,a)f(x)dx=∫(0,a)x^2dx-k∫(0,a)dx   即k=(1/3)x^3|(0,a)-ka整理有   k(1+a)=(1/3)a^3   解得:k=a^3/(3a+3)   即有∫(0,a)f(x)dx=a^3/(3a+3),a≠-1.   证毕.
点击显示
数学推荐
热门数学推荐
  • 语文
  • 数学
  • 英语
  • 科学
  • 作文